Angiogenesis induction in Buerger's disease: a disease management double-edged sword? - Fazeli, Bahare (Orphanet J Rare Dis, 2019)
Due to unknown aetiology of Thromboangiitis obliterans (TAO), its effectively treating is challenging. However, angiogenesis induction is one of the acceptable treatments for TAO patients. Recently, we have noticed that TAO patients who were under long-term treatment with angiogenesis-inducing medication showed considerable improvement in terms of healing chronic ulcers over the course of one to 2 years of treatment. However, some of them developed dermal gangrene despite the warming of their feet, with or without palpable pulses in the extremities, and with hair growth on the affected skin. Unfortunately, following the progression of dermal gangrene, some of these patients had to undergo amputation and limb loss. During histopathological evaluation, we detected some changes in the amputee TAO patients under long-term angiogenic medical treatment that were not present in amputee TAO patients who had not received any treatment for many years. The greatest pathological changes were observed in the microvascular of the skin, appearing as a proliferation of endothelial cells, NETosis and thrombus formation inside the vessels with proliferation of endothelial cells. The immunohistochemistry for CD31 and Ki67 as markers of vascular endothelium differentiation and cell mitosis confirmed the proliferation of endothelial cells. However, in the patients who had not received any treatment for years the typical pathology view of BD, including preserved vascular architecture with infiltration of inflammatory cells and inflammatory cells inside the thrombus, organised thrombus with recanalisation and intimal thickening was observed. Further longitudinal cohort studies regarding long-term treatment with angiogenic medications for TAO in different geographic areas are highly recommended.